Advances In HIV Research: Epidemiology, Pathogenesis, And Emerging Therapeutic Strategies - Sudipta Mukherjee; Mrinmoy Ghosh; Rituparna Chatterjee (International Journal of Pathogens, 2026)
Human Immunodeficiency Virus (HIV) remains a critical global health concern, infecting millions of individuals each year. The introduction of antiretroviral therapy (ART) has markedly improved disease outcomes by suppressing viral replication, restoring immune function, and extending patient longevity. Despite these advances, the complete eradication of HIV is hindered by the persistence of viral reservoirs, the emergence of drug-resistant strains, and disparities in healthcare accessibility. This review summarizes key developments in HIV epidemiology, virology, and pathogenesis, emphasizing recent innovations in ART, gene-editing technologies such as CRISPR, and ongoing vaccine research. Additionally, it explores the socioeconomic implications of the disease and highlights integrated strategies for prevention and control. Achieving long-term containment and eventual eradication of HIV will require a coordinated effort combining scientific breakthroughs with equitable public health policies
Keywords: CRISPR; HIV; antiretroviral therapy; epidemiology; vaccine development; viral pathogenesis